A systematic literature review of the policy and practice critiques of higher education exit exams: A global perspective - Teshome, Samson Worku (Bulletin of Educational Management and Innovation, 2025)
Background: Exit exams in higher education have been a subject of extensive debate, with proponents arguing that they ensure quality assurance and accountability, while critics highlight their potential negative impacts on students, educators, and institutions. This systematic literature review aims to synthesize the critiques of exit exams in higher education by analyzing 33 peer-reviewed studies published between 1994 and 2024. Method: The review employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework and PICO (Population, Intervention, Comparison, Outcome) criteria to ensure a rigorous and transparent selection process. A comprehensive search was conducted across multiple databases, including PubMed, ERIC, JSTOR, and Google Scholar, using keywords such as "exit exams," "higher education," "critiques," "equity," and "student well-being." Studies were screened based on predefined inclusion and exclusion criteria, with duplicate and irrelevant articles removed systematically. Data extraction was performed using a standardized form to capture key information, including study objectives, methodologies, geographic context, and specific critiques of exit exams. The extracted data were synthesized thematically to identify recurring patterns and trends. Key themes identified include the impact of exit exams on student stress and mental health, inequitable outcomes for marginalized populations, limitations in accurately assessing student competency, and misalignment with real-world skills. Findings: The findings reveal that exit exams often fail to account for diverse learning styles and may disproportionately affect marginalized students, while also potentially reinforcing systemic inequities and narrowing curricula. The review concludes with recommendations for policymakers and educators to consider alternative assessment methods that balance accountability with equity and student well-being, suggesting a need to reevaluate the role of exit exams in higher education.